1978
DOI: 10.1111/j.1471-6402.1978.tb00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Size, Satisfaction, and Productivity in Dual-Career Couples

Abstract: Responses by 196 couples—in which both spouses were members of the American Psychological Association—to a series of questions regarding domestic satisfaction, job satisfaction, and productivity were examined as a function of years since final degree and number of children in the family. There were consistent differences between the sexes in responses to these questions, indicating that wives were less satisfied and less productive than husbands in these couples. However, prior differences between groups in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 1 publication
1
31
1
1
Order By: Relevance
“…Greenhaus et al (1987) found that extensive time commitment to work is positively associated with work family conflict. Given that family work, house chores and childcare require many hours, we expect that the employed women have not enough time for family activities (Bryson et al, 1978). However, the question in this study is whether those who are teleworkers spend more time on family work.…”
Section: Literature Reviewmentioning
confidence: 41%
“…Greenhaus et al (1987) found that extensive time commitment to work is positively associated with work family conflict. Given that family work, house chores and childcare require many hours, we expect that the employed women have not enough time for family activities (Bryson et al, 1978). However, the question in this study is whether those who are teleworkers spend more time on family work.…”
Section: Literature Reviewmentioning
confidence: 41%
“…The effects appear to be stronger or more consistent for women than men, however. In a study of 196 dual career couples, increases in the number of children decreased satisfaction with time available for domestic activities for women, but had no affect for men (Bryson, Bryson and Johnson, 1978). Women who are employed, married, and parents also generally experience more conflict than women who are single or married but without children (Cooke and Rousseau, 1984;Hall, 1915;Hall and Gordon, 1973;Holahan and Gilbert, 1979b;Pleck et al, 1980).…”
Section: Results Of Work/family Conflict Studiesmentioning
confidence: 99%
“…shopping, cooking, cleaning, laundry) tends to get left undone or becomes "overtime" work. This creates the sense of overload and time pressure experienced to some degree by nearly all dual career families (Bryson et al, 1978;Epstein, 1971;Heckman, Bryson and Bryson, 1977;Holmstrom, 1972;Poloma and Garland, 1971;Yohalem, 1979). …”
Section: Income Was Also An Important Factor For Lifestyle Optionsmentioning
confidence: 99%
See 2 more Smart Citations